You are basically just working this problem backwards; the way you would find the zeros of the function.
Therefore, to start, make each equal to zero and do the opposite (+ or -) to each side.
-2=x and 2/3=x
0=x+2 and 0=x-2/3
In a function like this, we are usually given an equation like (x+#)(x+#) then we would set these to zero. However, since we are working backwards we are trying to get it in that (x+#)(x+#) form.
(x+2)(x-2/3)
2+2/3 = 2 2/3 or 2.667
2 x 2/3 = 4/3 or 1.334
Your quadratic function is now x^2+2.67x+1.334
or x^2+2 2/3x+4/3.
Hope I helped!